Chernobyl as an Exclusion Zone and Self-Knowledge [ According to Markiyan Kamysh’s Book Oformliandiia or Walk in the Zone - Pukhonska, Oksana (Poznańskie Studia Slawistyczne, 2022)
The presented article refers to Chornobyl as a text of culture which reflects such important problems as nature, human, ecology and memory. These problems the author of the research interprets through the literary work by contemporary Ukrainian writer Markiian Kamysh. The sources of literary contents of the writer’s book are based on his own experience of illegal travel to the Exclusion Zone, called stalkering. The hero of the book pays attention to the existential need of the contemporary human—how to establish a dialogue with nature, and to reveal yourself in it. Chornobyl in literature about environment is not only a symbol of catastrophe, but a space of finding yourself as part of nature, history and culture.